IMPLEMENTASI KEPEMIMPINAN KEPALA SEKOLAH DALAM PELAKSANAAN MUTU PENDIDIKAN DENGAN KONSEP MANAJEMEN BERBASIS SEKOLAH DI SD SWASTA PARULIAN 2 KECAMATAN TEGAL SARI MANDALA II - Mesty Hermauli Gultom; Sri Nurabdiah Pratiwi; Indra Prasetia (Jurnal Guru Kita PGSD, 2021)
Abstract: Implementation of Principal Leadership in the Implementation of Education Quality with School-Based Management Concepts at Parulian 2 Private Elementary School, Tegal Sari Mandala II District. This study aims to find out (1) How is the principal's leadership in improving the quality of education with the concept of school-based management in SD Swasta Parulian 2, (2) How are the results of implementing school-based management in SD Swasta Parulian 2, and (3) What are the supporting and inhibiting factors faced by the principal in implementing school-based management at the Parulian Private Elementary School 2. Data collection techniques in this study used interview, observation and documentation techniques. The data analysis technique used in this research is qualitative analysis through data reduction, data presentation and conclusion drawing. The results of this study indicate that: (1) The principal's leadership in improving the quality of education with the concept of school-based management at the Parulian Private Elementary School by carrying out activities such as: (a) School independence in meeting the availability of educators and education staff, facilities and infrastructure, ( b) School partnerships/cooperation with school internal and external parties, (c) School participation, (d) school transparency, and (e) school accountability. These 5 activities are effective in improving the quality of education in schools by means of school-based management. (2) the results of the implementation of school-based management at the Parulian 2 Private Elementary School can be seen from the principal's follow-up on: (a) school management, (b) student counseling guidance activities, (c) student extracurricular activities, (d) central management learning resources and (e) conducting relationship management to the school community. (3) the supporting and inhibiting factors faced by school principals in implementing school-based management at the Parulian 2 Private Elementary School, namely: (a) the high willingness of school residents, both teachers and educators, who expect good management in the future, but that willingness is not in line with knowledge school residents, namely teachers and educators about the concept of school-based management. Keywords:        Implementation of School-Based Management, School-Based   Management, Barriers to School-Based Management Abstrak: Implementasi Kepemimpinan Kepala Sekolah Dalam Pelaksanaan Mutu Pendidikan Dengan Konsep Manajemen Berbasis Sekolah Di Sd Swasta Parulian 2 Kecamatan Tegal Sari Mandala II. Penelitian ini bertujuan untuk mengetahui (1) Cara kepemimpinan kepala sekolah dalam meningkaatkan mutu pendidikan dengan konsep manajemen berbasis sekolah di SD Swasta Parulian 2, (2) Hasil implementasi pelaksanaan manajemen berbasis sekolah di SD Swasta Parulian 2, dan (3) Faktor pendukung dan penghambat yang dihadapi kepala sekolah dalam mengimplementasikan manajemen berbasis sekolah di SD Swasta Parulian 2. Teknik pengumpulan data pada penelitian menggunakan teknik wawancara, observasi dan dokumentasi. Teknik analisis data yang digunakan pada penelitian ini adalah analisis kualitatf melalui reduksi data, penyajian data dan penarikan kesimpulan. Hasil dari penelitian ini menunjukkan bahwa : (1) Cara kepemimpinan kepala sekolah dalam meningkaatkan mutu pendidikan dengan konsep manajemen berbasis sekolah di SD Swasta Parulian dengan melakukan kegiatan seperti : (a) Kemandirian sekolah dalam memenuhi ketersediaan tenaga pendidik dan kependidikan, sarana dan prasarana, (b) Kemitraan/kerjasama sekolah dengan pihak internal dan eksternal sekolah, (c) Partisipasi sekolah, (d) transparansi sekolah, dan (e) akuntabilitas sekolah. 5 kegiatan tersebut efektif dalam meninkatkan mutu pendidikan disekolah dengan cara manajemen berbasis sekolah. (2) hasil implementasi pelaksanaan manajemen berbasis sekolah di SD Swasta Parulian 2 ini dapat dilihat dari tindak lanjut kepala sekolah tentang : (a) manajemen sekolah, (b) kegiatan bimbingan konseling siswa, (c) penyelenggaraan ekstrakulikuler siswa, (d) pengelolaan pusat sumber belajar dan (e) melakukan manajemen hubungan ke masyarakat sekolah. (3) faktor pendukung dan penghambat yang dihadapi kepala sekolah dalam mengimplementasikan manajemen berbasis sekolah di SD Swasta Parulian 2 yakni : (a) banyaknya kemauan warga sekolah baik guru dan tenaga pendidik yang mengharapkan pengelolaan manajemen yang baik kedepannya, namun kemauan itu belum sejalan dengan pengetahuan warga sekolah yakni guru dan tenaga pendidik tentang konsep manajemen berbasis sekolah tersebut. Kata Kunci          :        Implementasi Manajemen Berbasis Sekolah, Berbasis Sekolah, Hambatan Manajemen Berbasis Sekolah